6x-2=-12+x

Simple and best practice solution for 6x-2=-12+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2=-12+x equation:



6x-2=-12+x
We move all terms to the left:
6x-2-(-12+x)=0
We add all the numbers together, and all the variables
6x-(x-12)-2=0
We get rid of parentheses
6x-x+12-2=0
We add all the numbers together, and all the variables
5x+10=0
We move all terms containing x to the left, all other terms to the right
5x=-10
x=-10/5
x=-2

See similar equations:

| 3+2^(x-5)=19 | | -1(x-1)+4x=-5 | | 3x-10=2x+5=x+20 | | 10^2x=125 | | 2+x/2-10=2/5 | | -7x+2-3x=2 | | 3x-7=-43-x | | 4p^2+25p=-25 | | 3+4m=15 | | 6p^2+7p=-1 | | -5+X+2x=-5 | | 7+x+2x=28 | | -3(y+3)=4y+26 | | -4w-22=3(w-5) | | 3(2+u)-u=4+2(u=1) | | -(2x+4)+7x=136 | | -(2x+4)+7x=1/6 | | 7p+6=5/6p-62 | | 5(x-7)=7x-49 | | 9(6m+7)=54m+63 | | 9=d-3.4 | | -6u+3(u+2)=15 | | -3x^2-13x-14=0 | | 3x+4-1=4+1x | | 3x+4-1=4+1x- | | 3.3(14.8r-8.1)=87.7 | | 7k−3k+11=0 | | 56^2+472k=-192 | | (x-7.5)+(x-12)=63 | | 4/5(m+7)=40 | | 100(x)+120(x)=760 | | x+17=23×= |

Equations solver categories